Stability of rhombohedral structure and improved dielectric and ferroelectric properties of Ba, Na, Ti doped BiFeO3 solid solutions. Issue 2 (15th January 2022) - Sharma, Subhash; Reshi, Hilal Ahmad; Siqueiros, Jesús M.; Raymond Herrera, Oscar
Abstract: A study of the (1-x)BiFeO3 -(x)Ba1/2 Na1/2 TiO2.75 (BFO-BNT) solid solutions obtained using the solid state reaction method, for different molar relative concentration of Ba1/2 Na1/2 TiO2.75 in the 0.0 ≤ x ≤ 0.12 composition range, is presented. The crystal structure and the dielectric and ferroelectric properties are studied in detail. Results of the Rietveld refinement of the X-ray diffraction data demonstrate that the system is single phase with R3c symmetry up to x = 0.09 while for x = 0.12, a small quantity of a secondary phase with P4mm symmetry appears. Scanning electron microscopy demonstrates that BNT presence promotes grain growth resulting in larger grains. Raman spectroscopy shows that, with increasing x, some of the A and E Raman modes slightly reduce their intensity while shifting in frequency, evincing the structural changes caused by the Ba, Na, and Ti incorporation on the BFO lattice. The X-ray photoelectron spectroscopy study confirms the successful substitution and gradual structural distortion in the samples. The improvement in dielectric properties with increasing BNT concentration can be attributed to stable dipole moment formation. Compared with pure BFO ceramics, doped BFO samples exhibit remarkably enhanced ferroelectric properties.